Information System Strategic Plan Using Zachman Framework and Raise at XYZ Vocational High School in Jakarta - Prakosa, Fajar (LPPM of STIMIK ESQ, 2018)
XYZ vocational School in Jakarta is also supported by Information Systems (IS) and other Information Technology (IT) devices in accelerating the business process. The current information systems require new proper improvement concept for further development. Combination of Zachman Framework and RAISE produces an Information System strategic plan that is focused and is in accordance with the management of vocational school.